Ultrathin bronchoscopy for solitary pulmonary lesions in a region endemic for tuberculosis: a randomised pilot trial. Issue 1 (December 2016) - Franzen, Daniel; Diacon, Andreas; Freitag, Lutz; Schubert, Pawel; Wright, Colleen; Schuurmans, Macé
Abstract Background The evaluation of solitary pulmonary lesions (SPL) requires a balance between procedure-related morbidity and diagnostic yield, particularly in areas where tuberculosis (TB) is endemic. Data on ultrathin bronchoscopy (UB) for this purpose is limited. To evaluate feasibility and safety of UB compared to SB for diagnosis of SPL in a TB endemic region. Methods In this prospective randomised trial we compared diagnostic yield and adverse events of UB with standard-size bronchoscopy (SB), both combined with fluoroscopy, in a cohort of patients with SPL located beyond the visible range of SB. Results We included 40 patients (mean age 55.2 years, 45 % male) with malignant SPL (n  = 16; 40 %), tuberculous SPL (n  = 11; 27.5 %) and other benign SPL (n  = 13; 32.5 %). Mean procedure time in UB and SB was 30.6 and 26.0 min, respectively (p  = 0.15). By trend, adverse events were recorded more often with UB than with SB (30.0 vs. 5.0 %, p  = 0.091), including extensive coughing (n  = 2), blocked working channel (n  = 2), and arterial hypertension requiring therapeutic intervention (n  = 1), all with UB. The overall diagnostic yield of UB compared to SB was 55.0 % vs. 80.0 %, respectively (p  = 0.18). Sensitivity for the diagnosis of malignancy of UB and SB was 50.0 % and 62.5 %, respectively (p  = 0.95). Conclusion UB is not superior to SB for the evaluation of SPL in a region endemic with tuberculosis, when combined with fluoroscopic guidance only. Trial registration ClinicalTrials.gov (Identifier:NCT02490059 ).